Book Heritage in Monasteries: The State of Monastic Libraries in Switzerland - A. Holenstein (Библиосфера)
Today, there are 65 active monasteries in Switzerland that were founded before 1800. They include women’s and men’s convents of 13 different orders of the Roman Catholic Church. These monasteries preserve a significant part of the written cultural heritage (manuscripts and prints) in Switzerland. Almost all monasteries are facing great challenges because of today’s major social and structural changes, which also have an impact on the book heritage of religious communities. The project Handbook of Monastic Libraries in Switzerland intends to create a survey of the current state of Swiss monastic libraries. The articles of this handbook describe the scope, content, condition and challenges of all monastic libraries. Well-known abbeys such as Einsiedeln, Engelberg or Saint Maurice as well as a large number of smaller women’s monasteries with less renowned book collections will be covered. The handbook aims at raising awareness for the preservation of monastic book heritage among politicians and the public.The paper will present first results from the work on the Handbook of Monastic Libraries in Switzerland and provide insight into actual conservation issues and research opportunities in Swiss monastic libraries.